Analisis Penentuan Hirarki Pusat Pelayanan Di Kabupaten Labuhanbatu Utara - Handayani, Siti Alifah; Pratama, Lucky Satria; Simbolon, Nur Aini; Amanda, Dhea; Gaol, Rista Y. Lumban; Siagian, Arnol P. (Yayasan Sagita Akademia Maju, 2024)
This research discusses determining the hierarchy of service centers in North Labuhanbatu Regency with a quantitative approach using the Analytic Hierarchy Process (AHP), Gravity Analysis, Scalogram and Centrality Index methods. The secondary data used was obtained from the Central Statistics Agency (BPS) of North Labuhanbatu Regency. This approach provides objective results in determining the priorities of service centers in the region. The research results show that there is a level of diversity in facilities in each sub-district, with Kualuh Selatan sub-district having the most facilities. Apart from that, the frequency of the existence of facilities also influences the centrality index and determining the hierarchy of service centers. These findings provide insight for local governments in more effective and efficient development planning.